Genetic characterization and fungicide resistance profiles of Botrytis cinerea in rooibos nurseries and pear orchards in the Western Cape of South Africa - Wessels, Andries Bernardus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2012.